Formative Assessment, Reality or Good Intentions? Case study in primary level teachers - Falcón Ccenta, Yárida (2021)
To develop the educational process framed within the competence approach, it is necessary to implement changes in the sub-processes, being of interest in this study the change in the evaluation of learning by the evaluation for learning, which implies a paradigmatic change that requires deconstructing a practice rooted in teachers. It is assumed that its successful implementation in the EBR will depend on the educational actors internalize and become aware of the need for this change in the evaluation, this would generate a positive predisposition to its application and the training, workshops and other strategies used to disseminate it are used to acquire the knowledge to support strategies for effective implementation. Faced with this pedagogical phenomenon of great social connotation and the reluctance and inefficiency observed in Peruvian schools, it isconvenient to analyze why the formative evaluation disseminated and embodied in official guide documents is not yet a reality in teaching practice. The answers were sought in a group of teachers involved in its implementation and were contrasted with the opinions of those who officially monitor its implementation in the classrooms, finding ignorance in the processes of this formative evaluation and a stubborn resistance to its application that underlies the teachers, who still use their own actions in other ways of evaluating.